The Acquisition and Processing of Formulaic Language: A Focus on Binomials and Collocations and the Effects of Congruency, Frequency and Learning Conditions - Altamimi, Abdulaziz (2021)
Research in corpus linguistics, psycholinguistics, and second language acquisition indicates that formulaic sequences pervade language (e.g., Erman & Warren, 2000; Howarth, 1998). Thus, mastery of them is crucial for maintaining fluent communication and achieving a native-like competence of the target language (Pawley & Syder, 1983). Although extensive research has been carried out on formulaic language, it is still not clear how factors such as cross-language congruency, frequency of exposure, type of exposure, and transparency influence the learning of formulaic language in an L2. For this thesis, I conducted three studies combining offline and online measures to gain greater insight into how knowledge of binomials and collocations is developed, as well as how these factors influence learning and processing. In the first study, I used self-paced reading and forced-choice tasks to investigate the role cross-language congruency and frequency of exposure play in the learning and processing of binomials. In this study, Arabic second language learners of English and English native speakers were presented with three types of binomial phrases: English-only binomials, Arabic-only binomials, and congruent binomials (occurring in both English and Arabic). The results revealed that both native and non-native speakers developed durable knowledge of the ‘correct’ order of binomials (i.e., fish and chips, not chips and fish) after only two exposures in a reading treatment. The results also showed that when a binomial phrase overlapped in the two languages, it was responded to more quickly and accurately. Frequency of exposure had a minimal effect on the learning outcomes, with no difference in performance between two and five exposures. The second and third studies investigated transparent collocations (Study 2) and opaque collocations (Study 3). In both studies, eye-tracking and offline measures were used and had three aims. The first aim was to discover the most effective learning condition to develop knowledge of transparent and opaque collocations for L2 learners and native speakers of English. The effectiveness of three learning conditions was evaluated: training- only (i.e., participants were explicitly asked to learn the target collocations), reading only (i.e., target collocations appeared four times in a text), and training plus reading (i.e., the collocations were presented before reading (a pre-reading exposure) and also occurred in reading). Participants took part in three phases (pre-reading, reading, and testing), and their performances were compared to a control group who only took part in the testing. The second aim was to investigate whether prior study of a collocation affected learners’ processing when encountering the same collocation during reading. The third aim was to investigate if online processing predicted learning gains of collocations. Overall, the results of Study 2 and Study 3 were consistent for both language groups. Training plus reading was the most effective learning condition for developing knowledge of the form and meaning of transparent and opaque collocations, while the reading-only condition was more effective than the training-only condition. With regard to processing, prior study of a collocation led to a processing advantage when encountering it during reading. Fixation patterns during pre- reading were indicative of performance for form recognition in Study 2, as well as indicative of performance for form recall and meaning recognition in Study 3; fixation patterns during reading were indicative of performance for form recognition (Study 3). The studies make a number of important contributions to the field. First, the findings show that congruency facilitates the learning and processing of formulaic language. Second, the results demonstrate that the type of exposure has the same effect for transparent and opaque collocations. Third, prior intentional study of a formulaic sequence results in substantial learning gains, when followed up with an incidental exposure. Finally, attention to a formulaic sequence during pre-reading contributes to learning.